Samuel Barber remembered : a centenary tribute - Dickinson, Peter, 1934- (Eastman studies in music., 2010)
Samuel Barber is one of America's most popular classical composers. His widely beloved works include Adagio for strings and Knoxville : summer of 1915. The main source for Samuel Barber remembered : a centenary tribute is a panoply of vivid and eminently readable interviews by Peter Dickinson for a BBC Radio 3 documentary in 1981. The interviewees include Barber's friends, fellow composers, and performers, notably Gian Carlo Menotti, Aaron Copland, William Schuman, Virgil Thomson, soprano Leontyne Price, and pianist John Browning. The book also includes three of the very few interviews extant with Barber himself. Dickinson contributes substantial chapters on Barber's early life and on Barber's reception in England. The book has a foreword by the distinguished composer and admirer of Barber, John Corigliano [Publisher description].